Prevalence of Obstetric Danger Signs during Pregnancy and Associated Factors among Mothers in Shashemene Rural District, South Ethiopia - Nega Terefe; Aderajew Nigussie; Afework Tadele (Journal of Pregnancy)
Introduction. Obstetric danger signs are those signs that a pregnant woman will see or those symptoms that she will feel which indicate that something is going wrong with her or with the pregnancy. Evidence on the prevalence of obstetric danger signs and contributing factors were crucial in designing programs in the global target of reducing maternal morbidity and mortality. Objective. To assess the prevalence of obstetric danger signs during pregnancy and associated factors among mothers in a Shashemene rural district, South Ethiopia. Methods. A community-based cross-sectional study design was conducted among 395 randomly selected women who gave birth in the last six months. A pretested interviewer-administered questionnaire was utilized. Data were cleaned, coded, and entered into Epi data manager version 4.1 and then exported to SPSS version 20. Bivariable and multivariable logistic regression analyses were employed to assess the association between independent variables with the outcome variable. Statistical significance was declared at p<0.05. Result. One hundred sixty-three (41.3%) of women had a history of obstetric danger signs during pregnancy. The most prevalent obstetric danger signs were vaginal bleeding (15.4%) followed by swelling of the body 12.7% and severe vomiting 5.3%. Women who have less than four times antenatal care visits were 6.7 times more likely to experience obstetric danger signs (AOR 6.7 (95% CI 3.05, 14.85)) compared to those who had antenatal care visit four times and above. Women who have inadequate knowledge of obstetric danger signs were 2.5 times more likely to experience obstetric danger signs during pregnancy (AOR 2.5 (95% CI 1.34, 4.71)), and primigravida women were 6.3 times more likely to have obstetric danger signs during pregnancy (AOR 6.3 (95% CI 2.61, 15.09)) compared to multiparous women. Conclusion. About half of the pregnant mothers have experienced at least one obstetric danger signs. Public health interventions on maternal health should give priority to the prevalent causes of obstetric danger signs, strengthening completion of four antenatal care visits and health education on obstetric danger signs for pregnant mothers at community level especially for primgravid women.